MITOS TENGET DALAM PELESTARIAN LINGKUNGAN HUTAN DI PURA PUSER SAAB NUSA PENIDA, BALI - Nyoman Sudipa (UHN IGB Sugriwa Denpasar, 2023)
The Puser Saab Temple Forest environment is located in Nusa Penida District, Klungkung Regency. The myth of tenget is able to preserve the existence of the forest because of the relation and symbolic power of the interaction between the community and the forest environment. Respect for the forest environment is carried out through rituals and protecting the forest as a form of personification of nature and the human body. Forest sacralization as social capital for forest sustainability and community survival. The myth of tenget is a form of respect and a way of communicating with nature and the environment. The existence of Tri Hita Karana as a concept of harmony to maintain the integrity of the Pura Puser Saab Forest environment. This study uses a qualitative approach with respondents from figures around the forest. This study aims to analyze the local wisdom of the community around Pura Puser Saab in preserving the forest environment. The methodology uses a qualitative approach and data collection is done through observation and structured interviews. Selection of respondents using purposive sampling technique. The results showed that the myth of tenget is a form of protection for the forest environment at Pura Puser Saab. The personification of nature such as the human body and humanizing nature makes the forest a social relation and social capital for society. Tenget is a process of sacredness that is built as a form of respect and communication between the community and the forest environment. The recommendation of this research is to strengthen local wisdom as social and spiritual capital